1987
DOI: 10.1159/000177273
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and Lipoprotein Levels of Newfoundland School Children

Abstract: Serum concentrations of total cholesterol, HDL, LDL, and VLDL cholesterol were measured in 1,033 boys and girls age 8–10 years and 14–16 years who were living in two geographically distinct areas on the East and West coast of Newfoundland. The respondents enrolled to this study were school children attending four schools selected at random from all schools in the area. Ninety percent of the invited students participated in the study. The Newfoundland children had higher total cholesterol levels than those repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Dyslipidemia in NL has been previously documented in several reports. School-aged children in the 1980s had higher total cholesterol levels compared to age, sex, and racially matched American children ( 15 ). A 1990s’ study on the rural Newfoundland population found that 61% of the subjects had hypercholesterolemia recorded in their medical records ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia in NL has been previously documented in several reports. School-aged children in the 1980s had higher total cholesterol levels compared to age, sex, and racially matched American children ( 15 ). A 1990s’ study on the rural Newfoundland population found that 61% of the subjects had hypercholesterolemia recorded in their medical records ( 16 ).…”
Section: Introductionmentioning
confidence: 99%